Analisis Cost Volume Profit Sebagai Dasar Perencanaan Laba Yang Diharapkan - Yunda Kusumaningayu; Rusman Soleman; Rizky Wahyu Utami Ohorella (Universitas 45 Surabaya, 2024)
Cost Volume Profit Analysis as a Basis for Expected Profit Planning (Case Study of Privately Owned Business